Benzimidazole-based N-heterocyclic carbene silver complexes as catalysts for the formation of carbonates from carbon dioxide and epoxides; Molecular Catalysis; Vol. 526 - Nawaz Z. Zahid; Ullah H. Habib; Gurbuz N. Nevin; Zafar M. N. Muhammad Naveed; Verpoort F. V. K. Frensis Valter Kornelius; Tahir M. N. Muhammad Nawaz; Ozdemir I. Ismail; Trovitch R. J. Ryan (2022, 2022)
Title screen